2011
DOI: 10.4049/jimmunol.1100519
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Expands Suppressive CD11b+ Gr-1int and Regulatory T Cells, including ST2L+ Foxp3+ Cells, and Mediates Regulatory T Cell-Dependent Promotion of Cardiac Allograft Survival

Abstract: IL-33 administration is associated with facilitation of Th type-2 (Th2) responses and cardioprotective properties in rodent models. However, in heart transplantation, the mechanism by which IL-33, signaling through ST2L, the membrane-bound form of ST2, promotes transplant survival is unclear. We report that IL-33 administration, while facilitating Th2 responses, also increases immunoregulatory myeloid cells and CD4+ Foxp3+ regulatory T cells (Treg) in mice. IL-33 expands functional myeloid-derived suppressor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
264
4
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(295 citation statements)
references
References 71 publications
25
264
4
2
Order By: Relevance
“…Previous studies have established the connection between IL-33 and an amelioration of T cell-mediated inflammation in different mouse models that were always accompanied by an enrichment of T reg cells (31,(45)(46)(47)(48). Our studies demonstrate that IVIG, through the presence of sialylated Fc interacting with type II FcRs, provides a source of IL-33 that can induce T reg -cell activation and expansion.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies have established the connection between IL-33 and an amelioration of T cell-mediated inflammation in different mouse models that were always accompanied by an enrichment of T reg cells (31,(45)(46)(47)(48). Our studies demonstrate that IVIG, through the presence of sialylated Fc interacting with type II FcRs, provides a source of IL-33 that can induce T reg -cell activation and expansion.…”
Section: Discussionsupporting
confidence: 63%
“…effector macrophages by sialylated Fc critically depends on production and secretion of IL-33 (29). Recent findings have indicated that IL-33 has a positive effect on T reg -cell stimulation and activation (31,32) and thereby contributes to the suppression of inflammation in a mouse model of experimental colitis (33). To test the possibility that sFc-induced production of IL-33 may also contribute to T reg -cell stimulation, we confirmed that naïve CD4 + T cells isolated from C57BL/6 wild-type mice, cultured for 3 d in the presence of anti-CD3 and anti-CD28 antibodies and TGF-β to specifically drive T reg -cell differentiation and then treated with IL-33, had a synergistic effect on T reg -cell differentiation as well as on Foxp3 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, with the now detailed understanding of the cellular and molecular mechanisms that control the balance between pro-and anti-inflammatory immune cells in AT, there is an opportunity to return to model systems to better define how obesity affects transplant outcomes. For example, study of how cytokines such as IL-4 and IL-33, which have been shown to prolong graft survival in lean cardiac allograft mice (57,58), may help delay graft rejection following transplantation in obese recipients by maintaining the type 2 immune response in adipose tissue, leading to new approaches to improve the overall success of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the relationship between allograft survival and the presence of immune cells by either removing specific cells from the recipient or by adoptively transferring cells into the recipient (1,2). Growing evidence suggests that myeloid-derived suppressor cells (MDSCs) play a crucial role in promoting cancer (3), suppressing autoimmune disease (4) and organ transplant rejection (5)(6)(7)(8). Thus, it would be interesting to examine the mechanisms by which MDSCs suppress immunological rejection and to identify the specific molecules involved; such knowledge could then be applied to clinical organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it would be interesting to examine the mechanisms by which MDSCs suppress immunological rejection and to identify the specific molecules involved; such knowledge could then be applied to clinical organ transplantation. Intensive research on MDSCs has shed light on the factors that influence their kinetics and function (8)(9)(10)(11). However, the exact mechanisms by which MDSCs suppress immune responses are unclear.…”
Section: Introductionmentioning
confidence: 99%